ANALISIS TERNAK UNGGULAN DAN PERTUMBUHAN SUBSEKTOR PETERNAKAN DI KABUPATEN OGAN KOMERING ULU TIMUR (JASEP, 2020)
The livestock subsector is one of the agricultural sectors developed by East OKU Regency and has an important role in providing animal protein needs for the people of East OKU Regency and surrounding areas. The purpose of this study is to determine the types of base livestock in East OKU Regency which contribute to regional development. The location determination is done intentionally (Puposive) because East OKU Regency is one of the self-sufficiency areas of meat with high natural resource and human resource potential. The method used in this research is literature study method using secondary data (Time Series). The results showed the growth of the livestock sub-sector in East OKU in 2012-2016 tended to be volatile. The livestock sub-sector which is the basis in the East OKU area is pigs with a LQ value of 4,868 and cattle with an LQ value of 1,862. Based on Shitf Share calculation, livestock that have the potential to increase economic growth are Broilers and Ducks.